2007
DOI: 10.1176/appi.ps.58.10.1324
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behavior Applied to Continuing Education for Mental Health Professionals

Abstract: The theory of planned behavior can improve and may be well suited to continuing education in psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…We retrieved the 52 studies from the original systematic review [8] reporting good psychometric properties and identified 20 new studies from the updated searches covering October 30, 2007 to October 31, 2010 [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33]. Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We retrieved the 52 studies from the original systematic review [8] reporting good psychometric properties and identified 20 new studies from the updated searches covering October 30, 2007 to October 31, 2010 [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33]. Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56]…”
Section: Resultsmentioning
confidence: 99%
“…Our review included 72 studies [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47], [48], [49], [50], [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77], [78], [79], [80], …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond simply training clinicians in the application of MBC, training may also be important to build buy-in for MBC implementation, as negative attitudes about evidence-based practices may limit their application (Aarons et al, 2012; Jensen-Doss & Hawley, 2010). Preliminary data suggest that MBC can be successfully introduced to clinicians using the theory of planned behavior (see Casper, 2007), which attempts to promote attitude and behavior change. However, few established protocols (or trainings) exist for using MBC to guide clinical decision–making in the context of psychotherapy.…”
Section: Challenges In Implementing Mbcmentioning
confidence: 99%
“…The TPB has been used in some studies in Africa on different studies on HIV/AIDS prevention (Jemmott et al 2010; Casper et al 2007). A study conducted by Jemmott et al (2007) in Xhosa adolescents in South Africa found that attitude and perceived behavioural control predicted the intention to use condoms while subjective norm did not.…”
Section: Discussionmentioning
confidence: 99%